BSADP mid term implementation report, volume 5 : compendium of research data - Bauchi State Agricultural Development Programme (Bauchi State : Bauchi State ADP, 1984)
The publication contains a series of project trials of different crops namely: sorghum, millet, maize, rice, cotton, cowpea, groundnut, and soya bean.
ne 19/08/2021
Ref.
Keywords: Research and development; Production management; Nigeria